2019
DOI: 10.1111/asj.13270
|View full text |Cite
|
Sign up to set email alerts
|

Growth of rumen papillae in weaned calves is associated with lower expression of insulin‐like growth factor‐binding proteins 2, 3, and 6

Abstract: This study aimed to characterize the relationship between the growth of rumen papillae in calves and the mRNA expression of insulin‐like growth factor‐binding proteins (IGFBPs) in the rumen papillae. The length of rumen papillae, the mRNA expression of IGFBPs in rumen papillae by quantitative real‐time PCR, and the presence of insulin‐like growth factors I and II (IGF‐I and II) by immunohistochemistry (IHC) were analyzed in nine Holstein calves divided into three groups: suckling (2 weeks, n = 3), milk‐continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…We observed that the IGFBP3 + EC appeared only in newborn calves considered to be functionally monogastric animals. The IGFBP3 encodes a protein that is known to inhibit the role of IGFs in cell proliferation [ 58 ]. This indicates that the disappearance of IGFBP3 + EC may facilitate the rumen epithelium development.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that the IGFBP3 + EC appeared only in newborn calves considered to be functionally monogastric animals. The IGFBP3 encodes a protein that is known to inhibit the role of IGFs in cell proliferation [ 58 ]. This indicates that the disappearance of IGFBP3 + EC may facilitate the rumen epithelium development.…”
Section: Discussionmentioning
confidence: 99%
“…The fixed papillae samples were rinsed and dehydrated in a series of ethanol baths and then deparaffinized in xylene. Each papillae sample was stained with hematoxylin and eosin (H&E) and then observed under a Leica S9 Stereo microscope (Leica Microsystems Inc., Buffalo Grove, United States) as described previously ( Nishihara et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it is possible that IGFBP might prevent BREC proliferation. Expression of IGFBP2 , IGFBP3 , and IGFBP6 in the rumen papillae of weaned calves was, respectively, 93%, 78%, and 85% lower than that in the rumen papillae of suckling calves (Nishihara et al., 2019). Therefore, we analyzed the effect of the IGFBP2 protein on BREC proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression analysis was performed by qRT‐PCR using SYBR ® Premix ExTaq™ II (Tli RNaseH Plus) (TaKaRa Bio) in a Thermal Cycler Dice ® Real Time System II (TaKaRa Bio). The primer sequences were described in our previous study (Nishihara et al., 2019); the PCR efficiencies were 0.8–1.2 for each primer pair, as determined by drawing standard curves using serial dilutions of pooled cDNAs. Beta actin (ACTB) and 18S were detected as reference genes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation